AN OVERVIEW OF THE COMMUNITY KNOWLEDGE LEVEL TOWARDS THE USE OF GENERIC DRUGS IN TUPA VILLAGE, NORTH BULANGO DISTRICT, BONE BOLANGO REGENCY, GORONTALO PROVINCE, IN 2022 - Abubakar, Fadlun; Yunus, Fitriah Ayu Magfirah; Hasili, Abdul Sulhadi (Sekolah Tinggi Farmasi Muhammadiyah Cirebon, 2024)
Generic drugs are medications with generic names, as defined by the Indonesian Pharmacopoeia and International Non-proprietary Names (INN) from the WHO, and they do not use trade names or manufacturer logos. Examples of these include amoxicillin and metformin. The public often perceives generic drugs to be inferior to patented drugs because of their relatively lower prices. The purpose of this study is to describe the knowledge level of the community about the use of generic drugs in Desa Tupa, Kecamatan Bulango Utara, Kabupaten Bone Bolango in 2022. This study employs a descriptive method using a quantitative approach. Data were collected through questionnaires that were distributed to 30 randomly selected respondents. A univariate analysis was conducted by creating frequency distributions to determine the community's awareness level regarding generic drugs. The survey results indicated that most residents of Desa Tupa have limited information about the use of generic drugs. The study concluded that, in terms of knowledge level about generic drugs, 30% of respondents had heard of generic drugs, 22% knew that generic drugs were named according to INN (International Non-proprietary Names), 11% understood that generic drugs are those that have expired patents, 9% recognize that generic drugs do not use brand names, and 28% are aware that generic drugs are more affordable than branded drugs.